2015
DOI: 10.1039/c5ra14640b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MRC2 and CD209 receptors as targets for photodynamic therapy of retinoblastoma using mesoporous silica nanoparticles

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…In the presence of retinoblastoma cells, porphyrin dimers may penetrate by passive diffusion through the cell membrane bilayer or interact with a mannose receptor (MRC2 or CD209) and be internalized by endocytosis . The mechanism of penetration of a porphyrin influences the subcellular localization of the PS, and thus its efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of retinoblastoma cells, porphyrin dimers may penetrate by passive diffusion through the cell membrane bilayer or interact with a mannose receptor (MRC2 or CD209) and be internalized by endocytosis . The mechanism of penetration of a porphyrin influences the subcellular localization of the PS, and thus its efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to the presence of its mannosyl moieties, compound 2 could potentially interact with one mannose receptor at the surface of cells, and cross the biological membrane by receptor‐mediated endocytosis ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Par ailleurs ceux-ci induisent une reconnaissance efficace du photosensibilisateur par les cellules tumorales surexprimant des récepteurs à sucre tels que des lectines [7]. Une porphyrine portant à sa périphérie trois groupes chimiques comportant des mannoses, conçue à l'Institut Curie, est reconnue par des cellules cancé-reuses de rétinoblastome (maladie rare du jeune enfant) surexprimant, sur leurs membranes, des récepteurs spécifiques du mannose [8,9]. La fixation de ce sucre sur le photosensibilisateur augmente notablement son efficacité photodynamique que ce soit in vitro ou in vivo [10].…”
Section: Les Photosensibilisateurs Limitation Des Composés Actuellemeunclassified
“…In 1989, Griegel et al [24] suggested the existence of sugar receptors at the surface of retinoblastoma cells, with binding specificities for b-galactose and a-mannose. More recently, two mannose receptors, MRC2 and CD209 have been identified as specific targets for PDT in Y79, WERI-Rb1 cells and primary human tumor tissues [25]. Mannosylated photosensitizers are expected to interact with these receptors and possibly penetrate, by receptor-mediated endocytosis, into retinoblastoma cells, provided that the positioning of the mannose moieties in these compounds allows molecular recognition [26,27].…”
Section: Introductionmentioning
confidence: 99%